IN SILICO STUDY OF ANTIDIABETIC ACTIVITY AND TOXICITY OF TRANS-ANETHOLE, FENCHONE, AND ESTRAGOLE - Susanti, Ni Made Pitri; Dewi, Luh Putu Mirah Kusuma; Bhadreswara, I Gede Rheza Wisnu (Journal Pharmaceutical Science and Application, 2024)
Background: An unhealthy lifestyle characterized by consuming foods with a high glycemic index can increase blood sugar levels significantly. Diabetes mellitus therapy using antidiabetic drugs in patients aims to help control blood sugar levels. Objective: This study aims to determine the affinity and interaction models of trans-anethole, fenchone, and estragole as test compounds against the target proteins pancreatic ?-amylase and dipeptidyl peptidase-4 (DPP-4) enzyme, as well as in silico toxicity prediction of the test compounds. Methods: This study used AutoDock 4.2 as a molecular docking method to evaluate the affinity and interaction models of the test compounds against the target proteins pancreatic ?-amylase (PDB ID: 2QV4) and DPP-4 (PDB ID: 3W2T) as a potential antidiabetic agent. In addition, the toxicity of these compounds was predicted using the Toxtree program with Cramer Rules, Benigni/Bossa, Verhaar Sceme, and Kroes TTC parameters. Results: The results showed that the test compounds had binding energies that showed their affinity to the target protein. The trans-anethole did not show any structural features indicating potential toxicity. Fenchone has the class III category for the Cramer Rules parameters, and estragole has a structural alert for genotoxic carcinogenicity based on the Benigni/Bossa Rulebase parameter. Conclusion: Trans-anethole, fenchone, and estragole have been observed to exhibit antidiabetic potential through their interactions with the pancreatic proteins ?-amylase and dipeptidyl peptidase-4 (DPP-4) enzyme, although their effectiveness is not as high as that of the native ligands. Additionally, further toxicity testing is required for the three compounds. Keywords:  Trans-anethole, Fenchone, Estragole, Molecular Docking, Antidiabetic